The Parents’ Role in Science Education During Covid-19 Pandemic Era - Sugito Sugito; Sri Mulyani Endang Susilowati; Hartono Hartono; Putut Marwoto (Universitas Negeri Semarang, 2021)
Teaching Learning during the Covid-19 pandemic era is carried out by online from home, so the parents’ role is absolutely necessary. This study aims is to analyze the parents role in children's science education at home during the Covid-19 pandemic era. The related science learning is to explain and to communicate efforts of risk reduction and impact of natural disasters. This study uses a qualitative design with a phenomenological approach. The research was carried out on the guardians of students at SMP Negeri 1 Bandungan for the 2020/2021 academic year. The guardians of the students as respondents were divided into three groups, namely group based on educational background, income level, and type of work. Collecting data using interview techniques, questionnaires, documentation, and observation. Data were analyzed by qualitative analysis. The findings of this study as follow. The parents’ with higher education levels and the parents’ with ASN/TNI Polri jobs is the best role plays as learner, partner, teacher, pioneer, role model and family nursing, but the income level of parents’ has no effect on their position as a learner and family nursing. It is Recommended to do further research on children psychological family nursing during the covid-19 pandemic era.